Feasibility and Accuracy of Robot-Assisted, Stereotactic Biopsy Using 3-Dimensional Intraoperative Imaging and Frameless Registration Tool. Issue 4 (29th April 2023) - Deboeuf, Louise; Moiraghi, Alessandro; Debacker, Clément; Peeters, Sophie M.; Simboli, Giorgia Antonia; Roux, Alexandre; Dezamis, Edouard; Oppenheim, Catherine; Chretien, Fabrice; Pallud, Johan; Zanello, Marc
Abstract : BACKGROUND: Robot-assisted stereotactic biopsy is evolving: 3-dimensional intraoperative imaging tools and new frameless registration systems are spreading. OBJECTIVE: To investigate the accuracy and effectiveness of a new stereotactic biopsy procedure. METHODS: Observational, retrospective analysis of consecutive robot-assisted stereotactic biopsies using the Neurolocate (Renishaw) frameless registration system and intraoperative O-Arm (Medtronic) performed at a single institution in adults (2019-2021) and comparison with a historical series from the same institution (2006-2016) not using the Neurolocate nor the O-Arm. RESULTS: In 100 patients (55% men), 6.2 ± 2.5 (1-14) biopsy samples were obtained at 1.7 ± 0.7 (1-3) biopsy sites. An histomolecular diagnosis was obtained in 96% of cases. The mean duration of the procedure was 59.0 ± 22.3 min. The mean distance between the planned and the actual target was 0.7 ± 0.7 mm. On systematic postoperative computed tomography scans, a hemorrhage ≥10 mm was observed in 8 cases (8%) while pneumocephalus was distant from the biopsy site in 76%. A Karnofsky Performance Status score decrease ≥20 points postoperatively was observed in 4%. The average dose length product was 159.7 ± 63.4 mGy cm. Compared with the historical neurosurgical procedure, this new procedure had similar diagnostic yield (96 vs 98.7%; P = .111) and rate of postoperative disability (4.0 vs 4.2%, P = .914) but was shorter (57.8 ± 22.9 vs 77.8 ± 20.9 min; P < .001) despite older patients. CONCLUSION: Robot-assisted stereotactic biopsy using the Neurolocate frameless registration system and intraoperative O-Arm is a safe and effective neurosurgical procedure. The accuracy of this robot-assisted surgery supports its effectiveness for daily use in stereotactic neurosurgery.